Tropical Deltas and Coastal Zones: Food Production, Communities and Environment at the Land and Water Interface 2010
DOI: 10.1079/9781845936181.0048
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of shrimp aquaculture systems in the coastal zones of Bangladesh and Vietnam: a comparison.

Abstract: Based on on-farm surveys implemented in the Ganges Delta in Bangladesh and the Mekong Delta in Vietnam, the dynamics of shrimp aquaculture in salinity-influenced coastal areas were analysed. Qualitative data were collected through interviewing both individual and group farmers in 2005 and 2006, as well as key informants and value chain stakeholders, to obtain an overview of the dynamics of salinity-influenced aquaculture in these two deltas. The first phase of the coastal area's agroeconomic evolution is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Compared to other Asian countries, which practice semi-intensive and intensive shrimp/prawn farming, Bangladeshi farmers are still dependent on extensive and improved extensive methods. There is huge potential to increase production by adopting best practice from other countries like China, Thailand, Indonesia and Vietnam (Joffre et al 2010). If Bangladesh seeks to increase yield by promoting intensive and semi-intensive methods, it must take adequate precautions to avoid the adverse effects experienced by other countries, particularly in terms of discharging antibiotics, fertilisers and other chemicals into adjacent water bodies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other Asian countries, which practice semi-intensive and intensive shrimp/prawn farming, Bangladeshi farmers are still dependent on extensive and improved extensive methods. There is huge potential to increase production by adopting best practice from other countries like China, Thailand, Indonesia and Vietnam (Joffre et al 2010). If Bangladesh seeks to increase yield by promoting intensive and semi-intensive methods, it must take adequate precautions to avoid the adverse effects experienced by other countries, particularly in terms of discharging antibiotics, fertilisers and other chemicals into adjacent water bodies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have focused on integrated agriculture and aquaculture models (Brennan et al, 2000;Bosma et al, 2006;Hoanh, 2006;Phong et al, 2006;Can et al, 2007;Nhan et al, 2007;Joffre and Bosma, 2009), differences in shrimp farming systems across countries (Hall, 2004) or economic analysis of the value chain and market (Macfadyen et al, 2005;Nguyen et al, 2005;Sinh and Khuyen, 2006;Hobbes et al, 2007;Sinh and Chanh, 2009). Surprisingly, there are few studies of livelihood strategies and decisionmaking among shrimp farmers (Hue and Scott, 2008;Joffre et al, 2010). This article focuses on the diversity of farmers' livelihood strategies, how they access various sources of capital to finance shrimp farming, to what uncertainties and vulnerabilities they are exposed and the pathways they have created to mitigate these risks and sustain their livelihoods.…”
Section: Introductionmentioning
confidence: 98%
“…27 -30 ºC; (Wyban, Walsh et al, 1995)), shrimp showed normal growth. Given a production of 3047 kg/ha and 2244 kg/ha (control and Lw-HUFA groups respectively) over an 8 week period, our experimental mesocosms mimicked a farming system of semi-intensive shrimp farmers in the Vietnamese Mekong Delta well (Joffre 2010). The mesocosms maintained low TAN, nitrite and nitrate concentrations during the entire experiment.…”
Section: Performancementioning
confidence: 99%
“…In natural systems without external feed input, autotrophic primary production reaches an average of 4 g carbon (C) m -2 d -1 (Brune 1991, Verdegem et al, 1999, Brune et al, 2003, an equivalent of 7-8 g organic matter (OM) m -2 day -1 . These extensive systems can produce approximately 300 kg shrimp ha -1 per 120 days, an equivalent of 30 g wet weight shrimp m -2 , or 7 g OM shrimp m -2 in 120 days (Joffre, 2010). In such systems, less than 1 % of the pond's primary production contributes to shrimp biomass production.…”
Section: The Potential Of Natural Food Contributionmentioning
confidence: 99%
See 1 more Smart Citation